2001
DOI: 10.1159/000047148
|View full text |Cite
|
Sign up to set email alerts
|

Liver Lipid Accumulation in Duck Embryos and Hatchlings Change with Parental Age<sup>1</sup>

Abstract: The purpose of this study was to investigate the effects of duck breeder age on liver lipid accumulation and yolk absorption and utilization in duck embryos (day 25 of incubation) and newly hatched ducklings. One breeder flock was monitored at 24 (young breeders), 31 (mature breeders and near peak egg production) and 47 (post peak egg production) weeks of age. Electron microscopy images of duck embryo liver slices revealed a significant change in hepatic lipid accumulation as a function of breeder age. More sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The results of viability rate in this work were in partial agreement with those reported by Washburn and Guill (1974) and Mc-Naughton et al (1978) that mortality rate appeared to be higher in chicks from young chicken breeders. Also, Braun et al (2001) reported that mortality was highest in ducklings from young breeders. The present results were slightly different in that viability of the ducklings initially increased with increased parental age and then decreased again at the older parental age.…”
Section: Duckling Performancementioning
confidence: 99%
“…The results of viability rate in this work were in partial agreement with those reported by Washburn and Guill (1974) and Mc-Naughton et al (1978) that mortality rate appeared to be higher in chicks from young chicken breeders. Also, Braun et al (2001) reported that mortality was highest in ducklings from young breeders. The present results were slightly different in that viability of the ducklings initially increased with increased parental age and then decreased again at the older parental age.…”
Section: Duckling Performancementioning
confidence: 99%
“…As shown in the current study, VLDL particles were altered in terms of components, i.e., lower CE:PRO and TG:PRO ratios for ducklings originating from 24-week-old breeders. This lower level of lipid components may partly explain the greater than expected yolk sac weights observed in these ducks as well as the reduction in liver lipid accumulation [11]; that is, we demonstrated in these ducklings that remnant yolk absorption is impaired, so this may have altered composition and level of lipoproteins derived from the yolk. The changes observed in VLDL may have resulted from differences in gene expression.…”
Section: Discussionmentioning
confidence: 52%
“…We [11] recently reported, however, that duck embryos from young parents have significantly less liver lipid accumulation as compared with duck embryos from older parents; therefore, suggesting that circulating lipoproteins may be altered. The present study was designed to investigate the changes in lipoprotein subfractions (VLDL and LDL) and their constituents, i.e., protein (PRO), TG, total cholesterol (TC), CE, phospholipids (PL), and the ratios of CE:PRO and TG:PRO.…”
Section: Introductionmentioning
confidence: 72%